KESULITAN KOMUNIKASI LISAN BAHASA DAERAH JAMBI MAHASISWA ASAL PAPUA: STUDI KASUS KELAS REGULER 4A - Nur Alimi; Agum Shohefi; Nabilla Fatin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the oral communication difficulties experienced by a Papuan student in understanding and using the Jambi regional language in the post-class. Differences in linguistic and cultural backgrounds caused difficulties in the process of daily social interaction. This study aimed to describe the forms of oral communication difficulties and the factors influencing the use of the Jambi regional language among a Papuan student in Regular Class 4A. This research employed a qualitative approach with a case study design. The research subject consisted of one Papuan student in Regular Class 4A. Data were collected through observation and interviews. The data analysis technique involved data collection, data reduction, data presentation, and conclusion drawing. The findings showed that the Papuan student experienced difficulties in understanding vocabulary, pronunciation, and sentence construction when communicating using the Jambi regional language. These difficulties were evident when communication occurred quickly and informally, causing the student to provide brief responses and participate less actively in conversations. In addition, the communication difficulties were influenced by limited language exposure, an underdeveloped second language acquisition process, first language interference, and social factors such as low self-confidence and limited social interaction. Therefore, oral communication ability is influenced not only by individual linguistic competence but also by the social environment that supports the language adaptation process.